Spectral Analysis Of Cutting Forces Data For XY Table Ballscrew Drive System - Abdullah, Lokman; Jamaludin, Zamberi; Chiew, Tsung Heng; Rafan, Nur Aidawaty; Shaaban, Azizah (Trans Tech Publications, 2014)
The utilization of spectral analysis for the purpose of investigating machining parameters in frequency domain has been widely practiced by group of researchers in engineering field. In this case the machining parameters involved are the cutting force parameter. By adapting spectral analysis to the cutting forces data, the researcher will have the access to identify the specific cutting forces exerted to the surface of the workpiece at each particular frequency under a set of frequency content. This paper is paying attention on the essential aspect on how to analyze the cutting forces data appropriately. It is recommended that those data need to be transformed first from the original form of cutting force data in time domain into the form of cutting force data in frequency domain. The outcome from this paper is in the form of graphical representation of cutting force data in frequency domain. It is obtained by applying Fast Fourier Transform (FFT) technique. To be more clear-cut, the result from this research work shows that the cutting force is directly proportional to the depth of cut and inversely proportional to the spindle speed of the end mill machine. The cutting force data later on will be used as an input disturbance for XY table ball screw drive system during the simulation process in the Matlab simulink diagram.